2019
DOI: 10.1080/13880209.2019.1680706
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing of Salvia miltiorrhiza after infection by its endophytic fungi and identification of genes related to tanshinone biosynthesis

Abstract: Context: Salvia miltiorrhiza Bunge (Labiatae) is a traditional Chinese herb. Endophytic fungi, which are biotic elicitors, can induce accumulation of secondary metabolites in their host plants.Objective: To analyze the interaction mechanism between S. miltiorrhiza and endophytic fungi.Materials and methods: Endophytic fungi U104 producing tanshinone IIA were isolated from the healthy disease-free tissue of root of S. miltiorrhiza by conventional methods. The endophytic fungus U104 of S. miltiorrhiza was co-cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Among these three, the SmCPS and SmHMGR2 genes were verified experimentally by RT-PCR studies in transgenic plants (Szymczyk et al 2016(Szymczyk et al , 2018. Similarly, the S. miltiorrhiza genes SmIDI, SmGGPPS, SmHMGS, SmHDR and SmDXR have also been experimentally-confirmed to respond to SA treatment (Hua et al 2012;Hao et al 2013Hao et al , 2015Jiang et al 2019;Yan et al 2009;Zhang et al 2010Zhang et al , 2016. SmDXS2 gene responded positively to overexpression of SmWRKY1, that is stimulated by SA treatment (Cao et al 2018).…”
Section: Distribution Of Sa Responsive Cis-active Elements Within Promentioning
confidence: 96%
“…Among these three, the SmCPS and SmHMGR2 genes were verified experimentally by RT-PCR studies in transgenic plants (Szymczyk et al 2016(Szymczyk et al , 2018. Similarly, the S. miltiorrhiza genes SmIDI, SmGGPPS, SmHMGS, SmHDR and SmDXR have also been experimentally-confirmed to respond to SA treatment (Hua et al 2012;Hao et al 2013Hao et al , 2015Jiang et al 2019;Yan et al 2009;Zhang et al 2010Zhang et al , 2016. SmDXS2 gene responded positively to overexpression of SmWRKY1, that is stimulated by SA treatment (Cao et al 2018).…”
Section: Distribution Of Sa Responsive Cis-active Elements Within Promentioning
confidence: 96%
“…In the present study, 24 TFs associated with tanshinones accumulation were obtained, including six NAC, four AP2/ERF, three WRKY, two MYB, and one MYB-related TFs. One ERF (Unigene0005368, ERF1B) and three WRKY (Unigene0002677, WRKY24; Unigene0005661, WRKY22; Unigene0019306, WRKY33) TFs related to the MAPK signaling pathway were identified, while one of them, WRKY33, was found to possibly regulate tanshinones accumulation (Jiang et al, 2019), suggesting that the possible regulatory role of the other three MAPK signaling pathway-related TFs as well as other tanshinones accumulation-related (Table S10). In addition, some members of the ERP, bHLH, and MYB transcription factor families have been previously identified to play important regulatory roles in tanshinone biosynthesis and accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the expression level of AACT is significantly correlated with tanshinone production [ 47 ]. SmDXS2 has been identified as a potential key enzyme in the pathway involved in targeted metabolic engineering to increase the accumulation of tanshinone in S. miltiorrhiza hairy roots [ 48 , 49 ]. CYP76AH1 has been demonstrated to catalyse the turnover of miltiradiene in tanshinone biosynthesis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic engineering can regulate secondary metabolism of S. miltiorrhiza through genetic modification of biosynthetic pathways [ 56 ]. Currently, most reports have focused on targeted metabolic engineering by key enzymes [ 8 , 49 , 57 ] or transcription factors [ 22 , 58 ]. Table 2 shows several genes (including SmGRAS3 , SmJAZ8 , and SmKSL ) and transcription factors (including SmWRKY2 , SmMYB36 , SmERF1L1 , SmERF115 , SmMYB98 , and SmWRKY1 ) that regulate the tanshinones biosynthesis.…”
Section: Discussionmentioning
confidence: 99%